PARTICIPAÇÃO E DELIBERAÇÃO NA GESTÃO PÚBLICA: desafios e potencialidades dos Fóruns Regionais de Governo - Flávia de Paula Duque Brasil (Universidade Federal do Maranhão, 2019)
The Minas Gerais Regional Government Forums were created to provide a channel for the demands of the population of the different regions of the state. The new participatory instance has developed, over the past four years, under the slogan of the Minas Gerais government (2015-2018) of "listening to govern". The objective of this study was to analyze the central characteristics of the institutional design and the participatory process, based on the theoretical reflections of Fung and Wright (2003) on Empowered Participatory Governance and Tarragó, Brugué and Cardoso Jr. (2015) on the construction of a Deliberative Public Administration. In the analysis, were identified potentialities and challenges in the implementation of the Regional Government Forums and raise reflections on its consolidation as a democratic innovation in the Minas Gerais management model.